Developing and Deploying OERs in sub-Saharan Africa: Building on the Present - Wright, Clayton R.; Reju, Sunday A. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2012)
Open educational resources (OERs) have the potential to reduce costs, improve quality, and increase access to educational opportunities. OER development and deployment is one path that could contribute to achieving education for all. This article builds on existing information and communication technology (ICT) implementation plans in Africa and on the experiences of organizations and initiatives such as the African Virtual University (AVU), OER Africa, the South African Institute of Distance Education (SAIDE), and the Teacher Education in Sub-Saharan Africa (TESSA) Project, to present one view of the benefits, challenges, and steps that could be taken to realize the potential of OERs in sub-Saharan Africa. Thus, the article focuses on the factors necessary for creating and sustaining a vision for OER development and deployment; developing and distributing resources with an open license; improving technology infrastructure and reducing the cost of Internet access; establishing communities of educational collaborators; sustaining involvement in the OER initiative; producing resources in interoperable and open formats; establishing and maintaining the quality of OERs; providing local context to address national and regional needs and conditions; informing the public about OERs; and taking the initiative to build on the knowledge, skills, and experiences of others. In order to assist educators and decision makers, links to a variety of resources are provided.